Analisis Efektivitas Penyaluran Dana Nonhalal Pada Lembaga Amil Zakat Terhadap Infrastruktur Sosial - Darmayanti Darmayanti; Putri Al Azzuri; Nani Astiani; Nurhamiza Harahap (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
The purpose of this study is to evaluate the impact of amil zakat institutions' non-halal fund distribution on social infrastructure. Quantitative research methodology is the approach employed. Secondary data are the kind used in this investigation. The Zakat Core Principle's Allocation to Collection Ratio (ACR) measurement ratio is employed in this approach to gauge how well a zakat institution is doing its zakat distribution. The financial statements of LAZ Rumah Zakat for the years 2020–2022 were the study's object. The findings demonstrated that from 2020 to 2022, the efficiency of nonhalal money distribution grew yearly. With a rate of 68% in 2021, the nonhalal money distribution proved to be quite effective. The efficiency of non-halal in 2022